CHARACTERISTICS OF STEAM BROWNIES WITH THE ADDITION OF SEAWEED FLOUR (Eucheuma cottonii) - Anisa Triwulandini; Tjipto Leksono; N. Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTThis study aims to determine the characteristics of steamed brownies with the addition of seaweed flour (Eucheuma cottonii) and to determine the best concentration of seaweed flour in steamed brownies. The concentration given consisted of 0, 15 and 20% seaweed flour. The test parameters observed were organoleptic. The best addition of seaweed flour to steamed brownies was found at a concentration of 20% with the characteristics of intact, neat, and bright brown color, specific aroma of brownies, sweet taste and soft and dense texture.Keywords: Steamed brownies, Characteristics, Seaweed flour (Eucheuma cottonii)